1995
DOI: 10.1111/j.1365-2893.1995.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C antibody in patients with chronic liver disease and hepatocellular carcinoma in Korea

Abstract: To investigate the contribution of hepatitis C virus (HCV) to chronic liver disease and hepatocellular carcinoma (HCC) in Korea, antibodies to HCV (anti-HCV) were tested by enzyme immunoassay in 1759 patients with chronic liver disease and HCC, and in 808 healthy adults. The prevalence of anti-HCV was 1.6% in 808 controls. Anti-HCV was present in 32 (7.7%) of 418 hepatitis B surface antigen (HBsAg)-positive and 128 (53.1%) of 241 HBsAg-negative patients with chronic hepatitis, 16 (6.0%) of 265 HBsAg-positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…HCV/HDV coinfection may also suppress HBV replication and thus lead to the "anti-HBc alone" serostatus [Liaw et al, 1991b;Fong et al, 1991;Fattovich et al, 1991;Liaw et al, 1992;Sheen et al, 1992;Shih et al, 1993;Francisci et al, 1995;Park et al, 1995;Jilg et al, 1995;Jylberberg and Pol, 1996;Hofer et al, 1998;Opravil et al, 1998]. This assumption is consistent with the frequent coincidence of anti-HBc and HCV markers and is supported by in vitro experiments [Shih et al, 1993].…”
Section: Chronic Infectionsupporting
confidence: 70%
“…HCV/HDV coinfection may also suppress HBV replication and thus lead to the "anti-HBc alone" serostatus [Liaw et al, 1991b;Fong et al, 1991;Fattovich et al, 1991;Liaw et al, 1992;Sheen et al, 1992;Shih et al, 1993;Francisci et al, 1995;Park et al, 1995;Jilg et al, 1995;Jylberberg and Pol, 1996;Hofer et al, 1998;Opravil et al, 1998]. This assumption is consistent with the frequent coincidence of anti-HBc and HCV markers and is supported by in vitro experiments [Shih et al, 1993].…”
Section: Chronic Infectionsupporting
confidence: 70%
“…No differences were found in summary OR according to type of controls. The crude OR for HBsAg and for anti-HCV-HCV RNA were lower than the adjusted ones in 6 of the 7 studies with secondgeneration anti-HCV/HCV RNA tests that reported OR adjusted for each marker and for demographic variables (Chang et al, 1994;Donato et al, 1997;Hadziyannis et al, 1995;Park et al, 1995;Stroffolini et al, 1992;Sun et al, 1996;.…”
Section: Resultsmentioning
confidence: 94%
“…A total of 32 case-control studies (Bile et al, 1993;Bruix et al, 1989;Cenac et al, 1995;Chang et al, 1994;Chuang et al, 1992;Cordier et al, 1993;Coursaget et al, 1992;Dazza et al, 1993;Di Bisceglie et al, 1991;Donato et al, 1997;Fukuda et al, 1993;Hadziyannis et al, 1995;Kaczynski et al, 1996;Kaklamani et al, 1991;Kew et al, 1997;Nomura et al, 1996;Okuno et al, 1994;Park et al, 1995;Pyong et al, 1994;Saito et al, 1990;Shin et al, 1996;Simonetti et al, 1992;Stroffolini et al, 1992;Sun et al, 1996;Tsai et al, 1996a;Xu et al, 1990;Yang et al, 1996;Yu, M.C. et al, 1997;Yu et al, 1991;Yu, S.-Z.…”
Section: Resultsmentioning
confidence: 99%
“…In Korea, the prevalence of HCV infection ranges from 1.3% to 1.6% and the virus is the agent secondarily responsible following HBV for chronic liver diseases (19, 20). This study is the first report to demonstrate an association between HLA and the susceptibility to HCV infection in the Korean population, who have a single ethnic background.…”
Section: Discussionmentioning
confidence: 99%